Application of Small Mobile Ground Station in UAV Location - Gao, Saisai; Tao, Zhu; Huang, Ying (Journal of physics. Conference series, 2019)
Aiming at the problem that UAV can't locate accurately in the areas where the satellite navigation signal is poor or even lost, this paper proposes to establish a mobile ground station positioning system to realize the precise positioning of UAV in such areas. Mobile ground station positioning system is a new positioning concept, as a supplement to satellite navigation and positioning system, and breakthrough to the existing ground-based reinforcement system fixed ground station, has greatly expanded the area and type of UAV mission execution, and further promoted the application of UAV in mission execution.